Dynamic RWX ACM Model Optimizing The Risk on Real Time Unix File System - PK Patra; Padma Lochan Pradhan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The preventive control is one of the well advance controls for recent security for protection of data and services from the uncertainty. Because, increasing the importance of business, communication technologies and growing the external risk is a very common phenomenon now-a-days. The system security risks put forward to the management focus on IT infrastructure (OS). The top management has to decide whether to accept expected losses or to invest into technical security mechanisms in order to minimize the frequency of attacks, thefts as well as uncertainty. This work contributes to the development of an optimization model that aims to determine the optimal cost to be invested into security mechanisms deciding on the measure component of UFS attribute. Our model should be design in such way, the Read, Write & Execute automatically Protected, Detected and Corrected on RTOS. We have to optimize the system attacks and down time by implementing RWX ACM mechanism based on semi-group structure, mean while improving the throughput of the Business, Resources & Technology. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7059